The Arctic Ocean Primary Production in Response to Amplification of Climate Change: Insights from 2003–2022 Satellite Data - Frolova, A. V.; Morozov, E. A.; Pozdnyakov, D. V. (Izvestiya. Atmospheric and oceanic physics, 2023)
Spaceborne merged multisensory OC CCI (ocean Colour Climate Initiative) data were employed to reveal changes in primary production (PP) in the Arctic Ocean (AO) from 2003 to 2022. The assessments were performed making use of the algorithm by Behrenfeld and Falkowski (1997) that assured, according to previous investigations, the coefficient of correlation between the retrieved and shipborne PP values equal to 0.8 and 0.75 for the deep and coastal ocean zones, respectively. The applied methodology of the satellite ocean color data processing permitted to account for the effect of cloud masking and determine the phytoplankton concentration within both overcast areas and coastal waters that are subject to significant influences of land- and river run-off. The results obtained indicate that since 2003 the PP over the entire AO has increased by +18.5%. This increase in PP was mostly due to the PP steady rise in the pelagic basin whereas within the AO coastal zone the PP level remained rather steady with only a slight negative tendency (–1.6%). In the marginal seas, the PP change proved to be differently directed, ranging between +32% (Laptev Sea) and –13.6% (Chukchi Sea) and exhibiting a rather low reliability of statistical characteristics. The observed two-decadal variations/tendencies of PP are discussed in light of the AO climate warming phenomenon.